Regulation of gap junction channels by infectious agents and inflammation in the CNS - Castellano, Paul; Eugenin, Eliseo A. (Frontiers in Cellular Neuroscience, 2014)
Gap junctions are conglomerates of intercellular channels that connect the cytoplasm of two or more cells, and facilitate the transfer of second messengers, small peptides and RNA resulting in metabolic and electrical coordination. In general, loss of gap junctional communication (GJC) has been associated with cellular damage and inflammation resulting in compromise of physiological functions. Recently, it has become evident that gap junction channels also play a critical role in the pathogenesis of infectious diseases and associated inflammation. Several pathogens use the transfer of intracellular signals through GJ channels to spread infection and toxic signals that amplify inflammation to neighboring cells. Thus, identification of the mechanisms by which several infectious agents alter GJC could result in new potential therapeutic approaches to reduce inflammation and their pathogenesis.